THE EFFECT OF COMPENSATION AND LEADERSHIP STYLE ON EMPLOYEE MOTIVATION AND PERFORMANCE - Hasyim, Abdul Malik (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
The purpose of this study was to analyze the effect of compensation and leadership style on employee performance, both directly and indirectly through work motivation. The sample was determined as many as 200 civil servants with a multi-stage techniquerandom sampling. Data were analyzed using the Structural Equatine Modeling (SEM) approach. The results of the analysis show that compensation and leadership style have a positive and significant effect on employee performance, both directly and indirectly through work motivation. Work motivation mediates compensation and leadership style in predicting employee performance.